The Risk Factors of Intensive Care Unit Admittance during First Attack of Acute Pancreatitis - Dale, Jonas; Omdal, Thomas; Lie, Stein A.; Iversen, Knut; Flaaten, Hans; Ovrebo, Kjell K. (Scientific Research, 2012)
Background: A proportion of patients with acute pancreatitis develop severe organ dysfunction requiring admittance in an intensive care unit. Patient characteristics associated with ICU admittance were evaluated in this consecutive series of patients. Methods: The clinical course of patients with first attack of acute pancreatitis in urban Norway between 01.01.1996 and 31.12.2006 was reviewed. Patient characteristics, comorbidity, pre hospital delay and likely aetiology of acute pancreatitis were analysed as risk factors for ICU admittance. Results: This study includes 565 patients, 299 women and 266 men (p = 0.089), with a median age of 60 years (range: 17 - 98). 50 (9%) of the patients were admitted to the ICU. Men were more at risk than women for ICU admittance (OR 2.34; 95% CI: 1.27 - 4.32). Patients with alcohol associated pancreatitis (OR 5.94; 95%, CI: 2.61 - 13.53), miscellaneous aetiologies (OR: 2.81, 95% CI: 1.02 - 7.73) and non-assessed aetiology (OR 2.71, 95%, CI: 1.26 - 5.82) were more at risk of ICU admittance than patients with bile stones associated pancreatitis. Pre hospital delay increased the risk of ICU admittance amongst patients with alcohol associated pancreatitis (OR 4.23; 95%, CI: 1.11 - 16.18). Two comorbid conditions conveyed increased risk (OR 8.78; 95%, CI: 1.87 - 41.22). The case fatality rate was 24% in the ICU and 1.6% in the ward (OR 20.01, 95% CI: 7.71 - 51.93). Conclusions: Aetiology of acute pancreatitis, especially alcohol, pre-hospital delay and male gender are associated with increased of risk of ICU admittance and increased fatality rate during first attack of AP.
Keywords: Pancreatitis; Intensive Care; Multiple Organ Failure